2014
DOI: 10.11648/j.sjph.20140203.18
|View full text |Cite
|
Sign up to set email alerts
|

Practice of Menstrual Hygiene and Associated Factors among Female Mehalmeda High School Students in Amhara Regional State, Ethiopia

Abstract: Introduction: Menstrual hygiene management has not received adequate attention in the reproductive health sectors in developing countries. In Africa the practice of menstrual hygiene management is still poor and the issue is under estimated. Due to poor menstrual hygiene management the adolescent girls are exposed for reproductive tract infection, school absenteeism and increase school dropout rate. Objectives: To assess the practice of menstrual hygiene and associated factors among female Mehalmeda high schoo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

9
30
7

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(46 citation statements)
references
References 6 publications
9
30
7
Order By: Relevance
“…This difference could be due to minimal communication in families about menstruation and menstrual hygiene issues. Contrary to the findings of this study, high knowledge about menstrual hygiene was obtained in a study done in Amhara, northern Ethiopia, which was 90.7 % [17], possibly due to information provided about menstruation and menstrual hygiene by schools and families.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…This difference could be due to minimal communication in families about menstruation and menstrual hygiene issues. Contrary to the findings of this study, high knowledge about menstrual hygiene was obtained in a study done in Amhara, northern Ethiopia, which was 90.7 % [17], possibly due to information provided about menstruation and menstrual hygiene by schools and families.…”
Section: Discussioncontrasting
confidence: 99%
“…The finding of this study was lower than studies conducted in Ethiopia and North western Nigeria which were 90.9 % and 88.7 %, respectively [15, 17]. Comparatively, lower level of practice of menstrual hygiene was recorded from similar study conducted on Gujjar girls it was indicated that only 3.1 % of the study participants practice good menstrual hygiene [24].…”
Section: Discussioncontrasting
confidence: 71%
“…The majority (46.3%) of the study participants reported that the main source of information about menses was their mother, which is similar to a study conducted in Nekemte, west Oromia and in sokota, Nigeria (14,17). But, it is, in contrast, to study in the Northern part of Ethiopia by…”
Section: Discussionsupporting
confidence: 75%
“…Population council office in which the majority (40%) of females received information about menses from their teacher instead of mothers(9%) (17). This difference is most probably because of cultural differences.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation